Antibiotics Used in Leptospirosis: A Narrative Literature Review - Amelia F. Dewi; Armen Ahmad; Fadrian (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Leptospirosis is an acute infectious disease that affects both humans and animals (zoonosis). This disease is caused by the Leptospira species, a bacterium with 250 serovar variations which thus detecting its cases is prominently challenging. In Indonesia, Leptospirosis is regarded as an iceberg phenomenon since such a challenge prevents this disease from being diagnosed in clinical practice, despite study data indicating that a significant percentage of reservoir rats in Indonesia are positive for Leptospira bacteria. As such, this disease has a high mortality of rats due to therapeutic delays. The usage of antibiotics is consequently considered an optimal therapy for leptospirosis. Antibiotics are chosen based on the clinical severity of the disease and should be administered as prophylaxis in high-risk groups in order to lower morbidity and mortality.